Finite Element Analysis for Improving the Bearing Capacity of Existed Strip Footings - Bahloul, Khaled Mohamed; El Siragy, Mohamed (الجمعية العلمية للمصممين, 2023)
Existing foundation is usually subjected to additional loads from different sources like increasing floor number, additional live load and eccentric loads. A result the foundation bearing capacity failure and excessive settlement are exhibited. Consequently, the aim of this work is to predict using a finite element method software (PLAXIS 3D) the reliability of increasing the loaded strip footing bearing area method on increasing the ultimate bearing capacity of the footing and decreasing settlement. The foundation soil used was dense sand (Dr=81%). Numerical analysis are validated by comparing the numerical results with results obtained using various analytical methods by Meyerhof, Hansen and Vesic. The effect of increasing footing size on the bearing capacity factor (N) is studied. Finally, the effect of load eccentricity was studied. It was concluded that ultimate load capacity is increased by as much as 67% in case of increasing footing area by 100% (ΔB/B = 1) with significant reduction in settlement that found to be 37%. As well, it was found that the bearing capacity factor (N) is reduced when the footing size increases which agree with previous works done on this issue. It was found also, that increasing footing area decreases significantly the load eccentricity effect on bearing capacity and modifying the bearing capacity failure from general to punching shear failure.
Keywords: القواعد الشريطية -- الهندسية الجيولوجية -- الخرسانة المسلحة